A ferroptosis-related gene signature and immune infiltration patterns predict the overall survival in acute myeloid leukemia patients - Yin, Zhao; Li, Fang; Zhou, Qinjun; Zhu, Jianfang; Liu, Zhi; Huang, Jing; Shen, Huijuan; Ou, Ruiming; Zhu, Yangmin; Zhang, Qing; Liu, Shuang (Frontiers in Molecular Biosciences, 2022)
Acute myeloid leukemia (AML) is sensitive to targeted therapy, with only a few anti-AML therapeutic targets identified to date. Ferroptosis is strongly related to drug resistance and carcinogenesis. However, its clinical value in AML is still unknown, and there are no known ferroptosis-based therapeutic targets. The present work involved retrieving ferroptosis-related genes (FRGs) and RNA-sequencing data from the FerrDb and The Cancer Genome Atlas (TCGA) databases. The ferroptosis-related gene ARNTL was observed to have high expression and poor prognosis in AML. Receiver operating characteristic curve (ROC) analysis revealed the predictive accuracy of the signature. The area under the time-dependent ROC curve (AUC) was 0.533 at one year, 0.619 at two years, and 0.622 at three years within the training cohort. Moreover, we found that the ARNTL expression is closely associated with tumor-infiltrating immune cells like the macrophages and NK cells. Inhibiting the ARNTL expression suppressed colony formation and induced ferroptosis in AML cells. After that, the survival prediction model constructed based on ARNTL accurately predicted the survival in AML, which could be a potential candidate for diagnosing and treating AML.